Measures of Educational Guidance: The assessment of Sensory Preferences for Learners of Portuguese as Second Language - Figueiredo, Sandra (2018)
The learning styles develop and transfer between them, constituting themselves as well as processes once they are subject to the development phases, caused mainly by the age advance. Sociological, motivational elements, sense of responsibility and other matters of internal and external nature are in the sphere of the learning style development. After a brief theoretical review, with the aim to address conceptually the styles of learning, will be presented some results, arising from the implementation of a questionnaire prepared for this purpose, which show the differences in preferences revealed by native and immigrant students. Will be discussed the evolution of sensory preferences in the context of Second Language learning, suggesting the hypothesis of a critical period for the type of sensory preference in the language learning. In other hand, will be also discussed the relation of the learning style with the academic success of students, and the consequence of that relationship as basic knowledge for an educative intervention that should guide and support measures for inclusion in a school that is increasingly a global institution concerning the type of students who hosts.